2017
DOI: 10.1039/c7ay01483j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of herbicide pyraclonil residue in rice, soil and water using high-performance liquid chromatography/tandem mass spectrometry

Abstract: A quick, reliable and sensitive analytical method for the confirmation and quantification of pyraclonil was developed using high-performance liquid chromatography/tandem mass spectrometry (HPLC-MS/MS) with an electrospray ionization source (ESI) in positive mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Acetochlor and butachlor analysis have been primarily performed on GC [32], HPLC [21], and GC-MS [33]. HPLC-MS/MS and GC-MS have higher sensitivity and precision and lower detection limits than traditional methods at trace levels in various matrices [34,35]. In addition, the combination of QuEChERS and mass spectrometry has been considered as the most sensitive, rapid, and reliable method for pesticide residue analysis in different matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Acetochlor and butachlor analysis have been primarily performed on GC [32], HPLC [21], and GC-MS [33]. HPLC-MS/MS and GC-MS have higher sensitivity and precision and lower detection limits than traditional methods at trace levels in various matrices [34,35]. In addition, the combination of QuEChERS and mass spectrometry has been considered as the most sensitive, rapid, and reliable method for pesticide residue analysis in different matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large and excessive use of herbicides, the problem of herbicide residues is gaining increasing attention. HPLC/MS is a routine method to determine the residue of herbicides in agrifoods and the environment . In a recent work, we tried to develop a quantitative method using UHPLC/MS to determine three herbicides (metolachlor, flufenacet and napropamide) in tea.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC/MS is a routine method to determine the residue of herbicides in agrifoods and the environment. [11][12][13][14] In a recent work, we tried to develop a quantitative method using UHPLC/MS to determine three herbicides (metolachlor, flufenacet and napropamide) in tea. As we know, matrix components of a sample usually negatively affect the analytical measurement of the target compound in HPLC/MS, the so-called matrix effect.…”
Section: Observation Of the Interferencesmentioning
confidence: 99%
“…Pathways for the metabolism of acetochlor in various crops (e.g., maize, soybeans, and cotton) have been worked out, and 2-ethyl-6-methylaniline (EMA) (Figure c) was reported to be the major aniline metabolite of acetochlor in corn and soybeans. Several studies have reported on the determination of metribuzin and acetochlor in wheat, corn, paddy, tomatoes, and soil, few reports described the detection of EMA in corn or soybeans, despite that EMA has been required to be taken into estimation considering its toxicological significance…”
Section: Introductionmentioning
confidence: 99%